Beat Merchants: the Origins, History, Impact, and Rock Legacy of the 1960's British Pop Groups - Clayson, Alan (London Blandford, 1995)
A true "insider" of the beat scene and author of the book that spawned the major motion picture Backbeat, Alan Clayson has created a comprehensive account of the origins, history, impact and legacy of the 1960s British pop groups including the Yardbirds, The Rolling Stones, the Kinks, and many more. Digging deep into this fascinating period, Clayson examines the sudden emergence of beatbands, their effects on music over the last three decades, and the reasons behind their widespread resonance both within and outside of the music scene. Informative as this book is, Clayson has also succeeded in showing us a "backstage" view inaccessible to most, and presents it in a way that will hold your attention page after page.
Includes bibliographical references (p. [313]-316) and index.
Keywords: 20th Century (1901-2000); Popular music; Music history